Binary tungsten-molybdenum oxides nanoneedle arrays as an advanced negative electrode material for high performance asymmetric supercapacitor. (1st November 2019) - Peng, Hui; Cui, Shuzhen; Xie, Xuan; Wei, Ganggang; Sun, Kanjun; Ma, Guofu; Lei, Ziqiang
Abstract: Herein, the novel binary tungsten-molybdenum oxides (W0.4 Mo0.6 O3 ) nanoneedle arrays have been prepared by a facile one-step hydrothermal method without adding any surfactant. The as-prepared W0.4 Mo0.6 O3 nanoneedle arrays can provide abundant exposed reaction active sites and utilize expedite transport channel to facilitate the diffusion of electrolyte ion. Thus, as an electrode for supercapacitor, it exhibits a high specific capacity of 115.7 mAh g −1 at the current density of 1 A g −1 and good rate performance. To achieve the high energy density of supercapacitor, an asymmetric supercapacitor is fabricated by using the W0.4 Mo0.6 O3 nanoneedle arrays as the negative electrode and the polygni multiflori caulis-based honeycomb-like carbon (PMCHC) as the positive electrode, which possesses a high output voltage of 1.5 V and an energy density of 20.2 Wh kg −1 at a high power density of 750.6 W kg −1, as well as good cycling stability. Such facile synthesis strategy and outstanding electrochemical behaviors imply that the binary metal oxides nanoneedle arrays is a promising electrode material for energy-storage system. Graphical abstract: Image 1 Highlights: Asymmetric supercapacitor is assembled based on novel W0.4Mo0.6O3 and PMCHC electrodes. The W0.4Mo0.6O3 nanoneedle arrays is prepared by a facile hydrothermal method. Polygni multiflori caulis-based carbon (PMCHC) has a unique honeycomb-like structure. PMCHC//W0.4Mo0.6O3 aqueous ASC with an extended operating voltage window of 1.5 V.